العالم الإسلامي والغرب : دراسة تحليلية لمظاهر التقارب والتباعد 2000-2012 = The Muslim world and the West: an analytical study of the aspects of rapprochement and discord (2000-2012) - Ahmed Ibrahim, Hassan (International Islamic University Press, 2014)
The present study attempts to shed some lights on the aspects of rapproachement as well as disagreement and aloofness between the Muslim world and the West.It also analyzes the efforts made in both directions since September 2001 and their political, social and economic implications for both worlds. The study then moves on to look into the prospects of the relationship between the Muslim world and the West. Finally it ends with putting forth a set of suggestions that may help nridge the profound gap between both worlds that has been created by belligerent ideas on both sides.